B-learning Modality: Basic Chess Course as a Strategy to Promote Reflective Thinking - Molina García, Amelia; Manzano Martínez, Jorge Armando (Emerging Trends in Education, 2021)
Encouraging the development of reflective thinking and the ability to make decisions has been a challenge for education, especially at the basic level. Motivated by this, this article presents the quasi-experimental research experience regarding a basic chess course, in the modality of b-learning, which constitutes a mediation strategy for the development of strategic or reflective thinking in students of the fifth grade of primary school. The purpose of the experience was to contribute to the comprehensive training of students, through extra-class activities in a fun way. The research is in progress and it uses a virtual platform, which includes the development of five learning units, aiming to improve cognitive skills with the use of strategically organized multimedia materials and resources. The psycho-pedagogical basis that guides the proposal is constructivist. The process of systematizing the experience in its pilot phase was carried out through a quantitative approach, pre-test / post-test, with which information was collected on the performance of the students, the performance in the activities, and it will be complemented with a survey on their perceptions regarding the educational process under the hybrid modality. It should be noted that once the experimentation phase of the proposal is concluded, the results will be contrasted with a control group. The hypothesis to be tested refers to the development of reflective thinking for decision-making through the practice of a chess course.Keywords: chess; hybrid mode; educational platform; reflective thinking; instructional design.